1996
DOI: 10.1111/j.2044-8260.1996.tb01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of obsessive—compulsive symptomatology to anxiety, depression and schizotypy in a clinical population

Abstract: The relationship of obsessive-compulsive symptomatology to anxiety disorders, mood disorders and schizophrenia continues to be controversial. In a sample of 117 psychiatric out-patients, we examined the relationship of obsessive-compulsive symptomatology to indices of anxiety, depression and schizotypy. The relationship between obsessive-compulsive symptomatology and schizotypy was found to be significantly higher than that between obsessive-compulsive symptoms and either anxiety or depression. These findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 48 publications
1
37
0
4
Order By: Relevance
“…Low correlation values of some items in the scale can be explained by the situation existing in scale development studies. In addition to this, t values of three items (16,23,24) were not statistically significant. In the first study for adaptation to Turkish, it was found that items 16 and 24 worked while item 23 did not work (7).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Low correlation values of some items in the scale can be explained by the situation existing in scale development studies. In addition to this, t values of three items (16,23,24) were not statistically significant. In the first study for adaptation to Turkish, it was found that items 16 and 24 worked while item 23 did not work (7).…”
Section: Discussionmentioning
confidence: 98%
“…As a result, non-significant t values may be the result of reverse coded items. The Cronbach alpha internal consistency coefficients of the scale in different cultures with different samples were calculated as 0.84 (21), 0.81 (22), 0.87 (23). The reliability coefficients of the scale are close to these values but a little bit lower in the Turkish sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrument has adequate levels of internal consistency, test-retest reliability and convergent validity (Feske & Chamless, 2000;Macdonald & de Silva, 1999). Two-factor analytic studies have suggested four component scales: (1) checking behaviour; (2) impaired control over mental activities; (3) contamination concerns, and (4) fear of losing motor control (Norman et al, 1996;Sanavio, 1988).…”
Section: Methodsmentioning
confidence: 98%
“…The scale was originally designed as a measure of psychosis proneness. It has demonstrated construct validity as a measure of schizotypy (Chapman & Chapman, 1985;Chapman, Chapman, & Miller, 1982), and adequate internal consistency (Eckblad & Chapman, 1983;Norman, Davies, Malla, Cortese, & Nicholson, 1996).…”
Section: Methodsmentioning
confidence: 99%